Front-of-package claims & imagery on fruit-flavored drinks and exposure by household demographics. (1st April 2022) - Musicus, Aviva A.; Hua, Sophia V.; Moran, Alyssa J.; Duffy, Emily W.; Hall, Marissa G.; Roberto, Christina A.; Dillman Carpentier, Francesca R.; Sorscher, Sarah; Wootan, Margo G.; Smith Taillie, Lindsey; Rimm, Eric B.
Abstract: Young children regularly consume sugary fruit drinks, in part because parents may falsely believe they are healthful due to front-of-package (FOP) claims and imagery. The goal of this study was to assess: 1) the prevalence of FOP claims/imagery on fruit-flavored beverages purchased by U.S. households with 0-5-year-olds, and 2) proportional differences in beverages purchased with FOP claims/imagery across household demographic groups. A content analysis of FOP claims/imagery (e.g., nutrient claims, fruit imagery) on beverages (n = 1365) purchased by households with 0-5-year-olds was conducted by linking beverage sales with FOP marketing data. Results were merged with purchasing data from a nationally representative sample of households (FoodAPS), and survey-weighted logistic regression was used to assess differences in the proportions of 100% juices and fruit drinks with specific FOP claims/imagery purchased by household race/ethnicity, income, and SNAP/WIC participation. The most common claims on fruit-flavored beverages included nutrient claims (fruit drinks: 73%; 100% juices: 68%; flavored waters: 95%), which most commonly highlighted vitamin C (35–41% across beverage categories) and the absence of sugar (31–48%). Most beverages also contained implied-natural claims (fruit drinks: 60%; 100% juices: 64%; flavored waters: 95%) and natural imagery (fruit drinks: 97%; 100% juices: 96%; flavored waters: 73%). A large proportion of fruit drinks and 100% juices purchased by households across all demographic groups contained FOP claims and imagery, with a few minor differences between racial/ethnic groups. In conclusion, most fruit drinks, 100% juices, and flavored waters purchased by households with 0-5-year-olds contained FOP claims and imagery that may lead consumers to believe the beverages are healthy and natural. FDA regulations should ensure parents are not misled by this marketing.